Evaluation of Key Indicators for Assessing and Grading Severity of Preeclampsia - Alshihabi, Radhia A.; Al-Saadi, Yasmin L. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Preeclampsia (PE) is a condition that is specific to pregnancy and has a substantial impact on the morbidity and mortality of the mother and the fetus worldwide. Currently, various markers may serve as possible predictors or markers for illness severity.Objectives: The present study aimed to identify and evaluate the key clinical indicators differentiating preeclampsia with and without severe features.Methods: The research included 90 pregnant Iraqi women who manifested preeclampsia subsequent to 24 weeks of gestation and were selected from Al-Elwiya Teaching Hospital for Maternity between April and June 2024. The patients were categorized into two groups: 45 with preeclampsia without severe features and 45 with preeclampsia with severe features. Key indicators assessed included blood pressure and laboratory parameters. Outcomes such as birth weight and FHR and complications, such as Caesarean section, intrauterine death, and eclampsia, were also determined.Results: The levels of Alanine Aminotransferase (AST), Alanine Transaminase (ALT), blood urea, and serum creatinine were significantly elevated in PE with severe features, while platelet counts were substantially reduced. Additionally, there was a noticeable rise in proteinuria; in PE without severe features, proteinuria reaches +2. While in PE with severe features, proteinuria exceeds +4. Pregnant women with preeclampsia with severe features had a lower birth weight of 2.32 kg, compared to those without severe features, who had a birth weight of 3.14 kg. The baseline fetal heart rate (FHR) decreased from 139 bpm in PE without severe features to 119 bpm in PE with severe features. PE with severe features is linked to greater maternal and fetal complications and shows increased rates of intensive care unit (ICU) (71.11%), Caesarean section (CS) (75.56%), intrauterine death (IUD)  (15.55%), and eclampsia (11.11%).Conclusion: The previously mentioned indicators AST, ALT, blood urea, serum creatinine, and proteinuria, in addition to fetal heart rate and birth weight, are valuable for assessing preeclampsia severity, highlighting the importance of monitoring.